2020
DOI: 10.1021/acsami.0c13825
|View full text |Cite
|
Sign up to set email alerts
|

In Situ One-Pot Synthesis of Fe2O3@BSA Core-Shell Nanoparticles as Enhanced T1-Weighted Magnetic Resonance Imagine Contrast Agents

Abstract: Ultra-small-sized iron oxide nanoparticles with good biocompatibility are regarded as promising alternatives for the gadolinium-based contrast agents, which are widely used as a positive contrast agent in magnetic resonance imaging (MRI). However, the current preparation of the iron oxide magnetic nanoparticles with small sizes usually involves organic solvents, increasing the complexity of hydrophilic ligand replacement and reducing the synthesis efficiency. It remains a great challenge to explore new iron ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 53 publications
1
36
0
Order By: Relevance
“…In addition, the stretching vibration peak of Fe–O at 604.5 cm −1 can be seen from the FT-IR of ES-MION9, but not in the FT-IR of PASP, indicating the existence of iron in ES-MION9. These results prove the successful synthesis of Fe 3 O 4 [ 38 ]. Additional file 1 : Fig.…”
Section: Resultssupporting
confidence: 59%
“…In addition, the stretching vibration peak of Fe–O at 604.5 cm −1 can be seen from the FT-IR of ES-MION9, but not in the FT-IR of PASP, indicating the existence of iron in ES-MION9. These results prove the successful synthesis of Fe 3 O 4 [ 38 ]. Additional file 1 : Fig.…”
Section: Resultssupporting
confidence: 59%
“…Since coordination number of iron ion is constant, the method to optimize the q is directly increasing the number of iron ions on the surface or introducing other magnetic ions with large amounts of unpaired electrons. Thanks to the controllable synthesis and development of new generation of surface ligands, various IONP with high surface-to-volume ratio, specific composition, and optimal surface coating have been developed to show high T 1 contrast and exhibit potential to achieve accurate tumor contrast imaging [ [48] , [49] , [50] ]. Recently, an undesirable structure, that is the presence of undesirable Fe (II) ion on the surface of IONP, have been noticed.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that Rh123@NiIO NPs were quickly metabolized through the kidneys and accumulated in the bladder and excreted from the body, which is likely due to the fact that the nanoparticles are less than the renal filtration threshold (6–8 nm). 39,50 Fluorescence imaging demonstrated the successful functionalization of NiIO NPs, further demonstrating that NiIO NPs are well metabolized in vivo . Therefore, NiIO NPs have great potential as multimode imaging nanoprobes, and the design idea of this integrated nanoparticle platform is of great significance for accurate clinical diagnosis.…”
Section: Resultsmentioning
confidence: 92%
“…The blocking temperatures at the peak of the FC/ZFC curves of NiIO NPs were all below 125 K, which was attributed to the extremely small size of nanoparticles. 14,39,40…”
Section: Resultsmentioning
confidence: 99%